Aflatoxin control strategies in the groundnut value chain in Ghana - Florkowski, Wojciech J.; Kolavalli, Shashidhara (International Food Policy Research Institute, 2013)
The objective of this paper is to identify strategies to reduce aflatoxin contamination of groundnuts in Ghana in order to enable the development of competitive and safe groundnut-based value-adding enterprises. We examine the quality assur-ance institutions with oversight on the groundnut value chain and the perceptions and practices of farmers and other agents along that value chain. We also test for aflatoxin contamination in groundnuts and groundnut products that have received varying degrees of processing.